INFORMASI DAN TEKNOLOGI DALAM PERSPEKTIF PENDIDIKAN ISLAM - Suriadi adi Samsuri (Program Studi Pendidikan Agama Islam, Universitas Majalengka, 2022)
The presence of educational technology is a necessity to overcome the problems of education in remote-lagging regions. Although initially only expected to be able to